Tenofovir‑associated renal toxicity in a cohort of HIV infected patients in Ghana - Nartey, E.T.; Tetteh, R.A.; Yankey, B.A.; Mantel‑Teeuwisse, A.K.; Leufkens, H.G.M.; Dodoo, A.N.O.; Lartey, M. (BMC Research Notes, 2019)
Objective: Tenofovir disoproxil fumarate (TDF) is a nucleotide analogue recommended in international HIV treatment guidelines. Purpose of this study was to estimate the long term effects of TDF on renal profile in a cohort of HIV patients in Ghana. Three hundred (300) consecutive HIV-positive patients who initiated TDF-based antiretroviral treatment in 2008 at the Korle-Bu Teaching Hospital were sampled. Creatinine clearance (CrCl) was calculated using the Cockcroft-Gault equation at baseline and renal impairment was defined as CrCl values of 30.0–49.9 mL/min (moderate renal impairment) and < 30 mL/min (severe renal impairment) as per institutional guidelines for renal function test. Results: Median follow up time was 2.9 years (IQR 2.3–3.4 years). At study endpoint, 63 participants (21.0% [95% CI 6.5–26.1]) recorded CrCl rate below 50 mL/min indicating incident renal impairment, made up of 18.3% moderate renal impairment and 2.3% severe renal impairment. Factors associated with incidence of renal impairment were increasing age, decrease in creatinine clearance rate at baseline, WHO HIV stage III/IV and participants with BMI of < 18.5 kg/m2. Patients with identified renal impairment risk factors at ART initiation should be targeted and monitored effectively to prevent renal
Research Article
Keywords: Tenofovir disoproxil fumarate; Renal dysfunction; Creatinine clearance; HIV; ART